What is the influence of grape products on liver enzymes? A systematic review and meta‐analysis of randomized controlled trials. (October 2022) - Ghaffar, Sadia; Naqvi, Mehak Ali; Fayyaz, Addeela; Abid, Mohammed Kadhem; Khayitov, Kakhramon Najmiddinovich; Jalil, Abduladheem Turki; Alsaikhan, Fahad; Hammid, Ali Thaeer; Al-Gazally, Moaed E.; Mohammadparast, Vida; Jannat, Behrooz; Nouri, Mehran
Abstract: Objective: This systematic review and meta-analysis were aimed to determine the effects of grape products on liver enzymes in adults. Methods: Databases including PubMed/Medline, Cochrane Library, ISI Web of Science, and Scopus were searched up to February 2021. Randomized clinical trials (RCTs) investigating the effect of grape products on serum concentrations of liver enzymes were included. Data were pooled using the random-effects model and weighted mean difference (WMD) was considered as the summary effect size. Results: Eight RCTs enrolling 291 participants met the inclusion criteria for this meta-analysis. The overall effect illustrated no significant change in serum levels of alanine aminotransferase (ALT) (WMD: − 2.04; 95 % CI: − 5.50 to 1.42; P = 0.24; I 2 = 72.5 %), and aspartate aminotransferase (AST) (WMD: − 1.40; 95 % CI: − 3.80 to 0.99; P = 0.25; I 2 = 76.0 %) in intervention group compared with the control group. Subgroup analyses revealed that the effect of grape products on ALT (WMD: − 4.97; 95 % CI: − 8.73 to − 1.21; P = 0.01) and AST (WMD: − 2.89; 95 % CI: − 5.69 to − 0.08; P = 0.04) levels was significant when the intervention period was equal or more than 12 weeks. Conclusion: Overall, grape products had no signiﬁcant effect on liver enzymes in adults. However, due to the low number of included studies, these findings must be interpreted with great caution. Larger, well-designed RCTs are still needed to further evaluate the capacity of the grape products as a complementary treatment to improve liver enzymes. Highlights: We examined the effects of grape products supplementation on liver enzymes in adults. Grape products did not have any significant effects on ALT and AST levels. More high-quality RCTs are needed to further clarify the effects of grape products supplementation on liver enzymes.